Sulfamoylbenzamide derivatives inhibit the assembly of hepatitis B virus nucleocapsids - Campagna, Matthew R; Liu, Fei; Mao, Richeng; Mills, Courtney; Cai, Dawei; Guo, Fang; Zhao, Xuesen; Ye, Hong; Cuconati, Andrea; Guo, Haitao; Chang, Jinhong; Xu, Xiaodong; et al. (Journal of virology, 2013)
Chronic hepatitis B virus (HBV) infection, a serious public health problem leading to cirrhosis and hepatocellular carcinoma, is currently treated with either pegylated alpha interferon (pegIFN-α) or one of the five nucleos(t)ide analogue viral DNA polymerase inhibitors. However, neither pegIFN-α nor nucleos(t)ide analogues are capable of reliably curing the viral infection. In order to develop novel antiviral drugs against HBV, we established a cell-based screening assay by using an immortalized mouse hepatocyte-derived stable cell line supporting a high level of HBV replication in a tetracycline-inducible manner. Screening of a library consisting of 26,900 small molecules led to the discovery of a series of sulfamoylbenzamide (SBA) derivatives that significantly reduced the amount of cytoplasmic HBV DNA. Structure-activity relationship studies have thus far identified a group of fluorine-substituted SBAs with submicromolar antiviral activity against HBV in human hepatoma cells. Mechanistic analyses reveal that the compounds dose dependently inhibit the formation of pregenomic RNA (pgRNA)-containing nucleocapsids of HBV but not other animal hepadnaviruses, such as woodchuck hepatitis virus (WHV) and duck hepatitis B virus (DHBV). Moreover, heterologous genetic complementation studies of capsid protein, DNA polymerase, and pgRNA between HBV and WHV suggest that HBV capsid protein confers sensitivity to the SBAs. In summary, SBAs represent a novel chemical entity with superior activity and a unique antiviral mechanism and are thus warranted for further development as novel antiviral therapeutics for the treatment of chronic hepatitis B.